Peranan kadar nitrit oksida (NO) darah dan asupan lemak pada pasien hipertensi dan tidak hipertensi - Pudji Astutik; Bambang Wirjatmadi; Merryana Adriani (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Hypertension is closely related to impaired endothelial dependent vasodilation due to decreasing availability of blood nitric oxide (NO) and high fat intake.Objective: To analyze blood NO and fat intake differences in patients with hypertension andnon hypertension.Method: The study was a cross-sectional design and sampling was carried out in Sidoarjo District Hospital. Subjects of the study were 24 patients aged between 40 to 65 years, which consist of 12 cases and 12 controls. Measurement of blood NO and recall of fat intake were performed.Results: Blood NO in hypertension andnon hypertension patients were 72.333 ± 40.511µM and 116.083 ± 46.962 µM respectively. Fat consumption in hypertension andnon hypertension were 51.52 ± 5.99 g and 41.65 ± 8.32 g respectively. Two independent samples t-test showed meaningful differences in the levels of blood NO (p=0.023) as well as fat intake (p=0.004) between the hypertension andnon hypertension patients.Conclusion: There is a difference in the levels of blood NO and fat intake in patients with hypertension andnon hypertension.